Sensing properties of the N,N'-dipentyl-3,4,9,10-perylenedicarboximide small molecule for different concentrations and solvents for sensor applications - Gündüz, Bayram (American Scientific Publishers, 2015)
In present study, optical parameters based on refractive index of the PTCDI-C5 molecule were calculated using the single oscillator model. Also, significant parameters such as long wavelength refractive index, average oscillator wavelength, lattice dielectric constant, ratio of the carrier concentration to the electron effective mass, carrier concentration and electron effective mass of the PTCDI-C5 molecule were obtained. Then, sensing properties of the PTCDI-C5 molecule for different concentrations and volume percents were investigated and the effects of the concentrations and volume percents on sensing parameters were investigated. Then, the optical properties of the solutions of the PTCDI-C5 semiconductor for different solvents were investigated. Finally, these parameters obtained were discussed for sensor applications and this study was compared with the similar and related studies in the literature. PTCDI-C5 can be used in the fabrication of various sensors due to good soluble, optical, sensitivity and response behaviour. Copyright © 2015 American Scientific Publishers
Keywords: One dimensional organic nanostructures; PTCDIC5; Sensing parameters; Sensitivity; Sensor applications; Wemple DiDomenico technique